Enhancing computational thinking skills in Thai middle school students through problem-based blended learning approaches - Aukkapong Sukkamart; Wassana Chachiyo; Manop Chachiyo; Paitoon Pimdee; Sangutai Moto; Piya Tansiri (Cogent Education)
This study aimed to compare Computational Thinking Skills (CTS) and Academic Achievement (AA) in students exposed to a Problem-Based Blended Learning (PBBL) model in a quasi-experimental setting. The research involved 43 Mathayom 2 students at a Rajabhat University Demonstration School in Thailand, selected through cluster random sampling. The participants were divided into an experimental group (n = 21) and a control group (n = 22). The CTS test employed a scoring rubric, and the AA test included multiple-choice questions. Data analysis used statistical measures such as mean, standard deviation (SD), and One-Way MANOVA. Results showed that the experimental group achieved significantly higher scores, with 91% in CTS and 89% in AA, compared to the control group’s 56% in CTS and 60% in AA. These findings demonstrate the effectiveness of the PBBL model in enhancing both CTS and AA in middle school students. This research contributes new insights by confirming that blended learning approaches can be effectively integrated into middle school education to foster critical thinking and academic success when combined with problem-based methodologies. The study provides evidence supporting the potential of innovative educational frameworks like PBBL in improving student outcomes, offering valuable implications for educators and curriculum designers.